Kinetics of the release of antimony trioxide from the backcoated textile preparation - Ghanem, Raed Ahmad (European Journal of Chemistry, 2015)
Segregation of antimony trioxide (ATO) from back-coated textiles was studied for two types of textile samples: A (ATO-Hexabromocyclododecane) and B (ATO-Decabromodiphenyl ether). Samples A was found to lose 5.3, 12, 28 and 39 %wt:wt of the amount of ATO originally present due to thermal ageing and UV exposure, respectively. Thermal ageing was performed at 25, 60 and 90 °C compared to 11.0, 17.3, 26.0 and 20.4 % wt:wt of ATO for sample B. The release follows first order kinetics with rate constants of 7.59×10-3, 1.89×10-2, 4.80×10-2 and 2.60×10-2 day-1, respectively, for type A and 9.20×10-3, 2.06×10-2, 4.10×10-2 and 3.83×10-2 day-1 for type B aged at 25, 60, 90 °C and UV exposure, respectively. Migration of ATO from the backcoated textile into simulated biological fluids was also studied for different type of samples under different ageing conditions using Head-over-Heels and contact blotting tests. The presence of biological fluids enhances the migration of ATO.